If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3)(x + -1) = 18 Reorder the terms: (3 + 2x)(x + -1) = 18 Reorder the terms: (3 + 2x)(-1 + x) = 18 Multiply (3 + 2x) * (-1 + x) (3(-1 + x) + 2x * (-1 + x)) = 18 ((-1 * 3 + x * 3) + 2x * (-1 + x)) = 18 ((-3 + 3x) + 2x * (-1 + x)) = 18 (-3 + 3x + (-1 * 2x + x * 2x)) = 18 (-3 + 3x + (-2x + 2x2)) = 18 Combine like terms: 3x + -2x = 1x (-3 + 1x + 2x2) = 18 Solving -3 + 1x + 2x2 = 18 Solving for variable 'x'. Reorder the terms: -3 + -18 + 1x + 2x2 = 18 + -18 Combine like terms: -3 + -18 = -21 -21 + 1x + 2x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -21 + 1x + 2x2 = 0 Factor a trinomial. (-7 + -2x)(3 + -1x) = 0Subproblem 1
Set the factor '(-7 + -2x)' equal to zero and attempt to solve: Simplifying -7 + -2x = 0 Solving -7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 0 + 7 -2x = 0 + 7 Combine like terms: 0 + 7 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-3.5, 3}
| q+14=8q+8*7 | | x+12+8x=30 | | 7n+39=11n-13 | | u+4=4u-8 | | (2x+3)(x+1)=18 | | c+2c-5-5c=7 | | 3(2m-3)=8(m+1) | | x^3+5x^2+7x+35= | | 1.2(4x-3.2)=2 | | 2x-4(x+2)=x(2x-1) | | (7x+3)=6 | | 6C(12)=48 | | (7x+3)= | | (4x-10x)-40+3=2(x-1) | | 5z-4z=48 | | 1x=2x-7 | | 2x-37=24 | | 3x^2-x=5 | | X=2x-7 | | 2x-3y=24 | | 6t-6=9t-36 | | k^2+4k-77=0 | | -9.3x+1.8=-52.8-1.5x | | 3.5+2x+5.5=10 | | 4x-10x-40+3=2(x-1) | | 7x+3x=6 | | (7)m-(9)m=(-12) | | x^2+5x+10=0 | | 3(w-2)-6w=-21 | | -2.06d+18=-10.48 | | 3a=144 | | 7m-9m=-12 |